A VALIDATED ANALYTICAL HPLC METHOD FOR THE QUANTIFICATION OF LINCOMYCIN HYDROCHLORIDE IN BULK AND SOLID DOSAGE FORM - Kumar, P. Rajeev; Rajeevkumar, Rekha (International Journal of Applied Pharmaceutics, 2017)
Objective: Develop a simple isocratic reverse phase high performance liquid chromatographic method (RP-HPLC) and validate for the determination of lincomycin hydrochloride (LMH) in bulk and pharmaceutical preparations. Methods: RP-HPLC quantification was carried out by using fine pack SIL RPC18 column. The mobile phase (methanol: water) was pumped at a flow rate of 1 ml/min in the ratio of 90:10 v/v and the eluents were monitored at 254 nm. Results: The retention time of the drug was 3.73 min and produced at a linear response in the concentration range of 5-25µg/ml. The percentage RSD was found to be below 2%. The LOD and LOQ were found to be 0.854µg/ml and 0.258µg/ml respectively. Conclusion: Validation of the method was performed for precision, accuracy, linearity, ruggedness, specificity and sensitivity to conform to ICH guidelines for valuation for analytical methods.